PENINGKATAN JUMLAH KUNJUNGAN WISATAWAN SEBAGAI DAYA TARIK WISATA PANTAI MARINA SEMARANG GUNA MENDUKUNG KESEJAHTERAAN MASYARAKAT - Suwarti Suwarti; Hani Krisnawati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The research in dynamic with the title “attractant Marina shore of Marina Semarang in increased the number of tourist visits” purposes aimed at finding an attractant of the Marina shore of Semarang with the analysis and identified using the tourist methods, accessibility, ameniti and ansilari. This study uses a kualitative method with 10 responses. The scpersonal technique used observation to the field, online interviews with data sources, the visitors and tourism and tourism later were documented in photographs. Kualitative analysis using data processing from data finding, then on alaysis and developed to the conclusion. From research results suggest that the beach Semarang beach is fairly good, but is less optimal in their breeding. In addition it was also found how the development efforts and difficulties in the management of which can be developed and is given advice for completion.